Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1080/15298868.2018.1430063
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of partisan identity fusion and prosociality during the 2016 U.S. Presidential Election

Abstract: We investigated the dynamics of identity fusion and prosocial behavior within political groups in the four weeks preceding and following the 2016 U.S. Presidential Election. The primary questions were whether a negative event (losing) would lead to a more pronounced increase in identity fusion, and whether identity fusion would predict prosocial giving. We found that while fusion gradually increased in the run-up to the election, there was no significant increase after the event for supporters of either party.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 47 publications
1
8
0
1
Order By: Relevance
“…With respect to the consequences of fusion, Whitehouse's rather narrow focus on violence, terrorism, and extreme behavior overlooks the fact that identity fusion may manifest itself in many other ways. For example, fusion has been linked to charitable giving to members of the in-group (Buhrmester et al 2018b;Misch et al 2018;Swann et al 2010b), donations of time and money to the community following a catastrophic earthquake (Segal et al 2018), adaptive coping in couples (Walsh & Neff 2018), endorsement of self-sacrifice in intergroup versions of the trolley dilemma (Gómez et al 2011a;Swann et al 2010a;2014b), expected life satisfaction following an election defeat or victory (Buhrmester et al 2012), plans to remain in the group (Gómez et al 2011b), curtailing medical aid to an out-group (Fredman et al 2017), endorsement of granting favors to one's twin (Vázquez et al 2017), undergoing sex reassignment surgery (Swann et al 2015), and endorsement of having the group fight for the self (Heger & Gaertner 2018b). One goal for a general theory of fusion would be to develop a common explanatory framework that could accommodate all of the diverse manifestations of identity fusion.…”
Section: Individual Difference In Acts Of Self-sacrificementioning
confidence: 99%
“…With respect to the consequences of fusion, Whitehouse's rather narrow focus on violence, terrorism, and extreme behavior overlooks the fact that identity fusion may manifest itself in many other ways. For example, fusion has been linked to charitable giving to members of the in-group (Buhrmester et al 2018b;Misch et al 2018;Swann et al 2010b), donations of time and money to the community following a catastrophic earthquake (Segal et al 2018), adaptive coping in couples (Walsh & Neff 2018), endorsement of self-sacrifice in intergroup versions of the trolley dilemma (Gómez et al 2011a;Swann et al 2010a;2014b), expected life satisfaction following an election defeat or victory (Buhrmester et al 2012), plans to remain in the group (Gómez et al 2011b), curtailing medical aid to an out-group (Fredman et al 2017), endorsement of granting favors to one's twin (Vázquez et al 2017), undergoing sex reassignment surgery (Swann et al 2015), and endorsement of having the group fight for the self (Heger & Gaertner 2018b). One goal for a general theory of fusion would be to develop a common explanatory framework that could accommodate all of the diverse manifestations of identity fusion.…”
Section: Individual Difference In Acts Of Self-sacrificementioning
confidence: 99%
“…The premise of our experimental design is to use the Dictator Game (DG) to compare how willing crowdworkers on MTurk are to cooperate with each other, with crowdworkers from a different platform, or with random strangers. We elected to use a DG because it reflects consequential real-world behavior (i.e., giving money), and while it is frequently conceptualized as a measure of generosity, in intergroup contexts it directly relates to social identification (Misch, Fergusson, & Dunham, 2018; Peysakhovich & Rand, 2017) and so can serve as a behavioral indicator of group alignment. To determine a realistic floor in giving, we also include an additional condition in which “donated” money is destroyed, that is, lost to all parties including the donating participant.…”
Section: The Use Of Online Labor Marketsmentioning
confidence: 99%
“…During an election year, political debates and animosity are constantly in the news (Iyengar et al, 2012), making political ideology more salient and members more aware of their differences. In fact, a recent study found that during the weeks prior to the U.S. Presidential election of 2016, there was an increase in identity fusion—where the self and political group identity merge as one (Misch, Fergusson, & Dunham, 2018), which then predicted prosocial ingroup behavior (e.g., donations to the party). This might also suggest more negative outgroup behavior would occur: Elections increase perceived political differences and incivility (He et al, 2019) and make it likely that teams have ideological ambivalence (e.g., some feel very positive about an election outcome, while others feel very negative; Ashforth, Rogers, Pratt, & Pradies, 2014; Pradies & Pratt, 2010), which can be destabilizing for group affect and outcomes (Pratt & Pradies, 2011).…”
Section: Future Directions For Political Ideology In Organizationsmentioning
confidence: 99%